Sosialisasi Gizi bagi Guru SDN 13 Konda untuk Mendukung Perilaku Makan Sehat Siswa Sekolah Dasar - La Ode Ahmad Yusran; Muh. Yasa (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2026)
A healthy diet in elementary school-aged children plays a crucial role in supporting physical growth, cognitive development, and academic achievement. However, low levels of nutritional understanding and teachers' limited ability to deliver nutrition education pose challenges in fostering healthy eating habits in students. This Community Service (PkM) activity aims to improve teachers' knowledge, skills, and attitudes in delivering balanced nutrition education to elementary school students. The activity was conducted at SDN 13 Konda over three days, involving eight teachers, using interactive outreach methods, discussions and questions and answers, hands-on practice in creating learning media, and evaluation. Evaluation instruments included pre-test and post-test questionnaires to measure teacher knowledge gains and observations of teachers' abilities in delivering nutrition materials. The results showed a significant increase in teachers' knowledge scores, from 62% before the outreach to 88% after the activity. Furthermore, teachers were able to design creative learning media such as educational posters, nutrition modules, storytelling, and interactive games based on balanced nutrition. The discussion also revealed challenges such as limited learning time and suboptimal parental support. Overall, this PkM activity effectively increased teachers' capacity in nutrition education and encouraged the implementation of active learning strategies in elementary schools. This program is expected to become a model for sustainable nutrition education that involves collaboration between schools and families to consistently shape healthy eating behaviors in students. Bayindir, N., & Gokce, M. (2024). Preservice primary school teachers’ perspectives on classroom-based mealtime as a tool for nutrition education and healthy eating habits. International Journal of Educational Researchers, 15(4), 69–80. https://ijer.inased.org/makale/5516 Dudley, D. A., Cotton, W. G., & Peralta, L. R. (2015). Teaching approaches and strategies that promote healthy eating in primary school children: A systematic review and meta-analysis. International Journal of Behavioral Nutrition and Physical Activity, 12, 28. https://doi.org/10.1186/s12966-015-0182-8 Elmas, C., & Arslan, P. (2020). Effect of nutrition education received by teachers on nutrition knowledge of students. Nutrition Research and Practice, 14(5), 532–539. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7520566 Fernanda, N. G., Taufiqurrahman, & Sayuningsih, E. (2023). The effect of education through PowerPoint media and infographic media on knowledge, attitude and action improvement on vegetables and fruits in school children at Elementary School Sidosermo 1 Surabaya. Journal of Nutrition Explorations, 1(1), 20–28. https://doi.org/10.36568/jone.v1i1.100 Gutkowska, K., Czarniecka-Skubina, E., & Hamulka, J. (2024). Is nutritional education in primary schools needed in the light of teachers’ perceptions on pupils’ nutrition knowledge? Annals of Agricultural and Environmental Medicine, 31(3), 371–381. https://doi.org/10.26444/aaem/186511 Jusriani, R., & Zulfitrawati. (2024). Edukasi gizi seimbang pada anak sekolah dasar. Locus Penelitian dan Abdimas, 1(2), 1–4. https://journal.tritunas.ac.id/index.php/LoA/article/view/277 Kurniasari, R., & Rahmatunnisa, R. (2021). Pendidikan gizi menggunakan media Nutriedutainment terhadap pengetahuan gizi seimbang anak sekolah dasar. Jurnal Gizi dan Kuliner, 1(2), 33–40. https://doi.org/10.35706/giziku.v1i2.4755 Maherawati, Hartanti, L., Suswanto, I., & Hernowo, K. (2025). Penerapan pola pangan sehat pada pelajar sekolah dasar menggunakan metode storytelling. Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 8(3), 626–637. https://riset.unisma.ac.id/index.php/jipemas/article/view/22775 Mumtazah Nadhiroh, A. K., Febrianti, A., Ultami, J. N., Ikhsan, M. A., & Hasibuan, R. (2025). Peningkatan pengetahuan gizi seimbang dan pola hidup sehat bagi siswa sekolah dasar melalui program edukasi interaktif di SDIT Swasta Al-Munaya: PKM. Bhakti Nagori, 5(2), 463–470. https://doi.org/10.36378/bhakti_nagori.v5i2.4595 Nurjannah, S., Masrikhiyah, R., & Rahmawati, Y. D. (2023). Pengaruh pendidikan gizi terhadap pengetahuan dan sikap tentang gizi pada siswa SDN Kedunguter 01 Brebes. Jurnal Ilmiah Gizi Kesehatan (JIGK), 5(1), 44–50. https://jurnal.umus.ac.id/index.php/JIGK/article/view/1316 Permadi, M. R., Mahendra, S. P., & Qondias, D. (2025). Perbedaan tingkat konsumsi zat gizi makro, status gizi dan indeks prestasi antara school feeding dan non school feeding anak usia sekolah dasar. Jurnal Edukasi Citra Olahraga, 5(1), 113–124. https://doi.org/10.38048/jor.v5i1.5239 Pratiwi, Z. A., Astuti, I. D., Apriah, N. N., & Inaroh, H. (2024). Parents’ and primary school teachers’ insights on balanced nutritious diet for children: A qualitative study. The Southeast Asian Journal of Tropical Medicine and Public Health, 54(Suppl. 2), 135–154. https://journal.seameotropmednetwork.org/index.php/jtropmed/article/view/984 Rafkhani, T. (2025). Peran media pendidikan gizi terhadap pengetahuan dan kebiasaan makan sehat pada anak sekolah. Nutrizione – Nutrition Research and Development Journal, 4(3), 31–39. https://doi.org/10.15294/nutrizione.v4i3.25104 Ruaida, N., Sammeng, W., & Haluruk, M. K. (2023). Pola makan dan status gizi anak sekolah dasar di SD Inpres 36 Rumah Tiga. Ghidza: Jurnal Gizi dan Kesehatan, 7(2), 305–315. https://doi.org/10.22487/ghidza.v7i2.1022 Safitri, N., & Hasanah, L. N. (2025). Pengaruh edukasi gizi seimbang terhadap peningkatan pengetahuan dan sikap gizi anak sekolah. Jurnal Kesehatan Tambusai, 6(1), 144–149. https://doi.org/10.31004/jkt.v6i1.40652 Safitri, Y., Juwita, D. S., & Zanisa, I. (2025). Edukasi pentingnya sarapan pagi bagi anak-anak sekolah dasar. Community Development Journal: Jurnal Pengabdian Masyarakat, 6(6), 6432–6435. https://journal.universitaspahlawan.ac.id/index.php/cdj/article/view/54748